1997
DOI: 10.1161/01.cir.95.5.1269
|View full text |Cite
|
Sign up to set email alerts
|

cGMP-Elevating Agents Suppress Proliferation of Vascular Smooth Muscle Cells by Inhibiting the Activation of Epidermal Growth Factor Signaling Pathway

Abstract: These results demonstrate that cGMP-elevating agents inhibit [3H]thymidine incorporation and thus the growth of VSMC, and this inhibition appears to attenuate EGF-activated signal transduction pathway by preventing Ras-dependent activation of Raf-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(142 citation statements)
references
References 30 publications
7
135
0
Order By: Relevance
“…Yu et al (12) reported that cGMPelevating agents suppress proliferation of VSMC, presumably through the activation of PKG and the phosphorylation of Raf-1. The major evidence presented that suggested the involvement of PKG was the sensitivity of the effects to the purported PKG inhibitor, KT 5823.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al (12) reported that cGMPelevating agents suppress proliferation of VSMC, presumably through the activation of PKG and the phosphorylation of Raf-1. The major evidence presented that suggested the involvement of PKG was the sensitivity of the effects to the purported PKG inhibitor, KT 5823.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ERK Activation by Selective Kinase InhibitorsPrevious studies have examined the effects of protein kinase inhibitors on MAP kinase activation in various cell types (12,57). Although it is evident that compounds previously believed to be selective for inhibiting PKA and PKG are not selective when used as described in intact cells (58,59), we were interested in determining whether or not there were any effects of these compounds on MAP kinase activity in the PKG-deficient and PKG-expressing adult RASMC.…”
Section: Effects Of 8-br-camp On Erk Activity In Rasmc-it Is Wellmentioning
confidence: 99%
“…To examine the potential role of cGMP-dependent protein kinase (cGPK) in the regulation of PAI-1 expression, cells were treated with KT5823, an inhibitor of cGPK previously shown to interfere with a variety of other actions of natriuretic factors and nitric oxide. 27,[43][44][45] Pretreatment of cells with 10 mol/L KT5823 for 10 minutes did not significantly alter Ang II stimulation or ANF suppression of PAI-1 mRNA levels ( Figure 6, bottom right). Thus, whereas cGMP appears to play an important role in the suppression of PAI-1 expression by natriuretic factors and nitric oxide, this effect of cGMP does not appear to require cGPK activity.…”
Section: Anf and Cnp Primarily Signal Via Natriuretic Peptide Receptomentioning
confidence: 93%
“…Although the MAPK pathway is a recognized signal transducer for neurotrophins, only recently have both ANP type -A and -C (CNP) and cGMP been shown to utilize this pathway. Both inhibition 73,74 and activation [75][76][77][78] of the MAPK pathway are seen in response to these molecules. The mechanisms underlying these responses are not fully understood.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%